Implementasi Akuntansi Zakat Infaq dan Shadaqah Berdasarkan PSAK 109 - Rozy Widhi Bayu Pratama; Ahmad Roziq (UPT Penerbitan Universitas Jember, 2017)
This research aims to know the accounting implementation of zakat, infaq and shadaqah based on PSAK NO. 109 whichfocuses on the presentation of the financial report on the institution of Zakat in Jember. This research is qualitative research ofcritical discourse analysis, a method that is done by collecting, preparing, and analyzing the data in the form of the financialstatements of the Organization so that it can eventually give a clear picture of the implementation of the accounting of religiousobligatory, infaq and charity based on PSAK NO. 109 on the institutions of zakat in Jember. Method of processing data usinginterviews, along with related documents and accompanied by one of the validity of the data i.e. triangulation. The resultsshowed that there are many differences in the accounting process as well as the presentation of the financial statementsconducted by institutions of zakat in Jember. Of the five institutions researched zakat Manager is still only one agency who hasapplied PSAK NO. 109.